Ethical content in artificial intelligence systems: A demand explained in three critical points - Bertoncini, Ana Luize Corrêa; Serafim, Mauricio C. (Frontiers in Psychology, 2023)
Artificial intelligence (AI) advancements are changing people’s lives in ways never imagined before. We argue that ethics used to be put in perspective by seeing technology as an instrument during the first machine age. However, the second machine age is already a reality, and the changes brought by AI are reshaping how people interact and flourish. That said, ethics must also be analyzed as a requirement in the content. To expose this argument, we bring three critical points - autonomy, right of explanation, and value alignment - to guide the debate of why ethics must be part of the systems, not just in the principles to guide the users. In the end, our discussion leads to a reflection on the redefinition of AI’s moral agency. Our distinguishing argument is that ethical questioning must be solved only after giving AI moral agency, even if not at the same human level. For future research, we suggest appreciating new ways of seeing ethics and finding a place for machines, using the inputs of the models we have been using for centuries but adapting to the new reality of the coexistence of artificial intelligence and humans.